Little Bee - Cleave, Chris; Cleave, Chris (New York : Simon & Schuster Paperbacks, 2010)
A haunting novel about the tenuous friendship that blooms between two disparate strangers--one an illegal Nigerian refugee, the other a recent widow from suburban London.
"Originally published in Great Britain in 2008 by Sceptre, an imprint of Hodder & Stoughton."
Includes reading group guide.
Includes bibliographical references.
Keywords: Young women -- Fiction; Nigerians -- England -- Fiction; Identity (Psychology) -- Fiction; Emigration and immigration -- Fiction; Refugees -- England -- Fiction